How has teaching effectiveness been conceptualized? Questioning the consistency between definition and measure - Taylor, Samantha; Thion, Stéphane (Frontiers in Education, 2023)
Teaching effectiveness (TE) research impacts educators and their careers, learners and the quality of education they receive, and administrators and the organizations they safeguard. However, there is a lack of consistency in how TE has been conceptualized: many papers used inaccurate or implied definitions of TE, or despite discussing and often measuring TE, did not define TE-other papers defined TE without proposed measures or provided measures of the concept without defining it. We found two dimensions of TE, student-focused (outcome) and educator-focused (input), and an existing TE definition evaluated as the strongest for both dimensions. Further, TE measurements may be summarized in five categories: student evaluation of teaching effectiveness (SETE), objective measures, peer review, administrative evaluation, and self-reflection. To conceptualize TE, our findings suggest pairing the TE studentfocused construct with SETE and objective measures, while the educator-focused dimensions of TE should be measured with peer review, self-assessment, and administrator evaluation. By consistently conceptualizing TE, researchers may contribute to rigorous research and work together to consistently add to the body of knowledge, thus furthering the quality of TE research.